Bodźcowy system regulacji cenowej przedsiębiorstw ciepłowniczych - Wierzbiński, Marcin (Incentive Regulation Model of Heat Producers and Distributors, 2007)
In the article the author proposes desired changes in the pricing regulation model of heat producers and distributors in Poland. The starting point of the article is setting up three main characteristics that optimal pricing regulation model should possess. Then the author specifies changes in pricing regulation model that would stimulate companies to renovate and invest in local heat systems. At the same time the proposed pricing regulation model has to protect customers against high level of heat price in Polish cities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 517-523